Novel High-Throughput Microwell Spectrophotometric Assay for One-Step Determination of Lorlatinib, a Novel Potent Drug for the Treatment of Anaplastic Lymphoma Kinase (ALK)-Positive Non-Small Cell Lung Cancer - Abdullah M. Al-Hossaini; Ibrahim A. Darwish; Hany W. Darwish (Medicina, 2023)
Background and Objectives: Lorlatinib (LOR) belongs to the third-generation anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitors. People who are diagnosed with ALK-positive metastatic and advanced non-small cell lung cancer (NSCLC) are eligible to get it as a first-line treatment option after it was given the approval by “the Food and Drug Administration (FDA)”. However, no study has described constructing high-throughput analytical methodology for LOR quantitation in dosage form. For the first time, this work details the construction of a high-throughput, innovative microwell spectrophotometric assay (MW-SPA) for single-step assessment of LOR in its tablet form, for use in pharmaceutical quality control. Materials and Methods: Assay depended on charge transfer complex (CTC) formation between LOR, as electron donor, with 2,3-dichloro-3,5-dicyano-1,4-benzoquinone (DDQ), as π-electron acceptor. Reaction conditions were adjusted, the CTC was characterized by ultraviolet (UV)-visible spectrophotometry and computational molecular modeling, and its electronic constants were determined. Site of interaction on LOR molecule was allocated and reaction mechanism was suggested. Under refined optimum reaction conditions, the procedures of MW-SPA were performed in 96-well assay plates, and the responses were recorded by an absorbance plate reader. Validation of the current methodology was performed in accordance with guidelines of “the International Council on Harmonization (ICH)”, and all validation parameters were acceptable. Results: Limits of detection and quantitation of MW-SPA were 1.8 and 5.5 µg/well, respectively. The assay was applied with great success for determining LOR in its tablets. Conclusions: This The assay is straightforward, economic and has high-throughput characteristics. Consequently, the assay is recommended as a valuable analytical approach in quality control laboratories for LOR’s tablets’ analysis.